Production of Micro Nanofibrillated Cellulose from Prerefined Fiber via a Dry Dielectric Barrier Discharge (DBD) Oxygen Plasma-Treated Powder Precursor - Katarina Dimic-Misic; Bratislav Obradovic; Milorad Kuraica; Mirjana Kostic; Huy Quang Lê; Matea Korica; Monireh Imani; Patrick Gane (Journal of Natural Fibers)
Cellulose is a strong contender for the development of sustainably resourced biodegradable material composites supporting circular economy. Nanofibrillar cellulose-comprising materials are among the most promising lignocellulose derivatives. Currently, their production capacity and economy are hindered by high chemical and energy consumption, the latter primarily during mechanical fibrillation of native fiber in aqueous suspension and the negative limitation of very low solid content associated with the gel-like properties of the resulting final product. The application of oxygen gas barrier discharge (DBD) plasma on dry cellulose fiber, as reported here, is considered novel in achieving onward nanofibrillation. At this early stage, though, simple laboratory DBD equipment precludes the study of overall efficiency. Example fiber was taken from paper pulp manufacture but may not be limited to wood source. The oxygen plasma was seen to etch the microcellulose fiber structure, simultaneously oxidizing the glue-functioning hemicellulose, rendering it soluble, so that nanopolymer crystalline-based cellulose fibrils can be readily released at the surface of the host refined microfiber at the point of application, forming micro nanofibrillated cellulose structure (MNFC) at previously uneconomic higher solid content. Eliminating the need for liquid water during precursor process treatment is considered potentially transformative with respect to production feasibility, end-product transportation and application.